The role of regulatory T cell (Treg) subsets in gestational diabetes mellitus. (July 2014) - Schober, L.; Radnai, D.; Spratte, J.; Kisielewicz, A.; Schmitt, E.; Mahnke, K.; Fluhr, H.; Uhlmann, L.; Sohn, C.; Steinborn, A.
Summary Physiological changes during normal pregnancy are characterized by an inflammatory immune response and insulin resistance. Therefore, we hypothesize that gestational diabetes mellitus (GDM) may be caused by an inappropriate adaption of the maternal immune system to pregnancy. In this study we examined the role of regulatory T cell (Treg) differentiation for the development of GDM during pregnancy. We used six‐colour flow cytometric analysis to demonstrate that the total CD4+CD127low+/−CD25+ forkhead box protein 3 (FoxP3+) Treg pool consists of four different Treg subsets: naive CD45RA+ Tregs, HLA‐DR−CD45RA− memory Tregs (DR− Tregs) and the highly differentiated and activated HLA‐DRlow+CD45RA− and HLA‐DRhigh+CD45RA− memory Tregs (DRlow+ and DRhigh+ Tregs). Compared to healthy pregnancies, the percentage of CD4+CD127low+/−CD25+FoxP3+ Tregs within the total CD4+ T helper cell pool was not different in patients affected by GDM. However, the suppressive activity of the total CD4+CD127low+/−CD25+ Treg pool was significantly reduced in GDM patients. The composition of the total Treg pool changed in the way that its percentage of naive CD45RA+ Tregs was decreased significantly in both patients with dietary‐adjusted GDM and patients with insulin‐dependent GDM. In contrast, the percentage of DR−‐memory Tregs was increased significantly in patients with dietary‐adjusted GDM, while the percentage of DRlow+ and DRhigh+ memory Tregs was increased significantly in patients with insulin‐dependent GDM. Hence, our findings propose that alterations in homeostatic parameters related to the development and function of naive and memory Tregs may cause the reduction of the suppressive capacity of the total Treg pool in GDM patients. However, as this is an exploratory analysis, the results are only suggestive and require further validation.